Demonstration of Self-Powered Accelerometer Using Piezoelectric Micro-Power Generator - Bong, Yu Jing; Kok, Swee Leong (2013)
This paper demonstrates the operation of a self-power vibration measurement system. A piezoelectric material in the form of a cantilever is being used as a generator which harvest energy from ambient vibration source and transform into useful electrical output. The vibration sources is measured with a MEMS based accelerometer, which is powered up by the transformation of electrical energy derived from the mechanical vibration source itself. It has shown that at a resonant frequency of 78 Hz with an acceleration level of 1g (9.81 m/s2), the piezoelectric generator is able to produce rms output voltage of 5.20 V and successfully operating ADXL335 with the assistance of energy harvesting conditioning IC, LTC3588-1 equipped with rectifying as well as DC-to-DC step-down functions.